From Vox Ferus to Canine Posthuman: Becoming a Singing Dog - Jelena Novak (Sound Stage Screen)
In this article I discuss the reworking of the demarcation line between human and animal through the vocal sphere by referring to a dog as an "animal of interest." I draw attention to a number of recent works—paintings, performance pieces, and operas—where the figure/construct/representation of the dog and dog-human relation serves as the engine of the piece. My focus is the representation of humans that "go out of themselves," acquiring in the process animal characteristics. I am especially intrigued by how this "going out of oneself" is reflected in the voice, and whether there is something that could be called animal/dog voice and what would its characteristics be.